Who benefits from R0 resection? A single-center analysis of patients with stage Ⅳ gallbladder cancer. Issue 3 (September 2019) - Chen, Chen; Wang, Lin; Zhang, Rui; Li, Qi; Zhao, Ya-Ling; Zhang, Guan-Jun; Li, Wen-Zhi; Geng, Zhi-Min
Abstract: Objectives: Most patients with gallbladder cancer (GBC) present with advanced-stage disease and have a poor prognosis. Radical resection remains the only therapeutic option to improve survival in patients with GBC. This study aimed to analyze the prognostic factors in patients with stage Ⅳ GBC and to identify a subgroup of patients who might benefit from R0 resection. Methods: A total of 285 patients with stage Ⅳ GBC were retrospectively analyzed at our institution from January 2008 to December 2012. Factors potentially influencing the prognosis of GBC after surgery were analyzed by univariate and multivariate analyses. Results: The 1-, 3-, and 5-year overall survival rates were 6.6% (15/229), 0.9% (2/229), and 0 (0/229), respectively. Ascites (relative risk [ RR ] = 1.631, 95% confidence interval [ CI ]: 1.221–2.180, P = 0.001), pathological grade ( RR = 1.337, 95% CI : 1.050–1.702, P = 0.018), T stage ( RR = 1.421, 95% CI : 1.099–1.837, P = 0.000), M stage ( RR = 1.896, 95% CI : 1.409–2.552, P = 0.000), and surgery ( RR = 1.542, 95% CI : 1.022–2.327, P = 0.039) were identified as independent risk factors influencing prognosis. The median survival time (MST) was significantly higher in patients undergoing R0 resection than in those undergoing R1/R2 resection (6.0 vs . 2.7 months; P < 0.001). In subgroup analyses, stage ⅣA patients benefited from R0 resection (MST for R0 vs . R1/R2, 11.0 vs . 4.0 months; P = 0.003), while R0 resection had a significant survival benefit than R1/R2 resection in patient with stage ⅣB GBC without distant metastasis (MST for R0 vs . R1/R2, 6.0 vs . 3.0 months; P = 0.007). Conclusion: Ascites, pathological grade, T stage, M stage, and surgery were independent risk factors influencing prognosis in patients with stage IV GBC. N2 lymph node metastasis did not preclude curative resection, and radical resection should be considered in patients with stage Ⅳ GBC without distant metastasis once R0 margin was achieved.